2015
DOI: 10.1111/bcpt.12484
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin, an Analgesic Used Against Cancer‐Associated Neuropathic Pain: Effects on Prostate Cancer Progression in an In Vivo Rat Model

Abstract: A major problem associated with clinical management of cancer is controlling the accompanying pain, and various analgesics are in common use for this purpose. Recent evidence suggests that some of the targets of analgesics, such as ion channels and receptors, may also be involved in the cancer process, thereby raising the possibility that such use of some analgesics may impact upon cancer itself. The main aim of this study was to determine whether gabapentin, a common adjuvant analgesic in current use against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…In vivo, local injection of the highly specific VGSC blocker, tetrodotoxin (TTX), into primary tumours significantly reduced metastases to lungs and prolonged survival 14 . In contrast, proliferative activity in vitro and in vivo was not affected by VGSC blockage consistent with the notion that primary tumorigenesis (ie proliferation) and metastasis (ie invasion) are controlled differently, even partially independently 15‐18 . Finally, quantitative analysis of “receiver operator characteristics” (ROC) in human biopsy tissues suggested that Nav1.7 mRNA expression had sufficient selectivity and specificity to serve as an effective biomarker of PCa 6 …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In vivo, local injection of the highly specific VGSC blocker, tetrodotoxin (TTX), into primary tumours significantly reduced metastases to lungs and prolonged survival 14 . In contrast, proliferative activity in vitro and in vivo was not affected by VGSC blockage consistent with the notion that primary tumorigenesis (ie proliferation) and metastasis (ie invasion) are controlled differently, even partially independently 15‐18 . Finally, quantitative analysis of “receiver operator characteristics” (ROC) in human biopsy tissues suggested that Nav1.7 mRNA expression had sufficient selectivity and specificity to serve as an effective biomarker of PCa 6 …”
Section: Introductionmentioning
confidence: 78%
“…Mat‐LyLu and AT‐2 cells were grown to near confluence and serially passaged every 7‐14 days (up to 15‐20 passages), as described earlier 2,15 . All cells were seeded into 100‐mm Falcon tissue culture dishes and grown in an incubator at 37°C, 100% relative humidity and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in our study, the developed model reflects the release patterns of the leuprolide microsphere, so it can be used in variety of situations which are for comparative evaluation of the drug delivery system with different release patterns and for the prediction of the PK–PD relationship based on the release profile. Our model is simpler than Lim and Salem’s [ 20 ]. Continuing these trials and errors, when the constant of the Hill equation was introduced for describing the PD profile of testosterone, the compensation effect of testosterone could be expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Dunning observed the appearance of prostate cancer in male Iar:COP rats, and Dunning R-3327 adenocarcinoma is a spontaneously occurred prostate tumor found in male Iar:COP rats. In this study, Iar:COP rats were used for PK–PD studies in the prostate disease model [ 20 ]. All the rats were divided into six groups: a vehicle-administered group, a solution-administered group, and an SR-administered group, for rats with and without prostate cancer (5 rats per group) and were maintained on a 12 h dark–light cycle at ambient temperature (19 ± 1 °C) and relative humidity (50 ± 5%) with free access to water and food.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent evidence suggests that anesthetics that target VGSCs, e.g., ropivacaine, may also inhibit cancer cell invasion ( Baptista-Hon et al, 2014 ). Furthermore, the voltage-gated Ca 2+ channel-targeting antiepileptic drug gabapentin, which may also inhibit VGSCs ( Zhang et al, 2013 ), has recently been shown to inhibit invasion and metastasis of prostate cancer cells at high doses ( Bugan et al, 2015 ). Finally, a recent study published in June 2015 (after the search period ended) has shown that lidocaine inhibits Na + current, extracellular signal-regulated kinase (ERK) phosphorylation and cellular invasion of SW620 colorectal cancer cells in vitro ( House et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%